SYNCHRONOUS AND ASYNCHRONOUS LEARNING ACTIVITIES AS ALTERNATIVE DISTANCE LEARNING MODELS THAT ARE ORIENTED TO OUTCOME-BASED EDUCATION - Dianna Ratnawati; Hasnul Azwan Bin Azizan; Mohammad Omar AL-Momani (Jurnal Dinamika Vokasional Teknik Mesin, 2023)
The learning model for teacher professional education program is carried out online by utilizing a learning management system which is divided into synchronous and asynchronous learning activities. The combination of these two activities is expected to optimize the quality of online learning, but in practice the success of this distance learning model often encounters obstacles both internal and external factors including network constraints, devices used, time management due to busy activities, differences in competence in digital literacy and student data literacy. , as well as constraints on achieving timespend in synchronous and asynchronous activities. Obstacles that arise as obstacles in learning activities need to be evaluated and solutions sought. This study aims to analyze the learning constraints in synchronous and asynchronous activities and find alternative solutions to support the achievement of outcomes based education. The method used is a case study through qualitative analysis. The research subjects were students of the teaching profession program in mechanical engineering concentration positions. The results of the study show that synchronous activities support students learning quickly but need to be supported by a stable network, quality devices, time management and human resources with good technological literacy and digital literacy. Whereas asynchronous provides breadth in the flexibility of learning activities but requires precision and consistency so that you don't get bored easily and require activeness in learning activities. It can be concluded that the effectiveness of distance learning is by collaborating synchronous and asynchronous learning proportionally and mutually reinforcing so that the quality of online learning can be guaranteed and the goals of the teaching profession program can be achieved